Differentiation potential of mesenchymal stem cells from equine bone marrow cultured on hyaluronic acid-chitosan polyelectrolyte multilayer biofilm - Listoni, Amanda J. [UNESP]; Arruda, Isadora [UNESP]; Maia, Leandro [UNESP]; Barberini, Danielle J. [UNESP]; Martins, Ian [UNESP]; Vasconcellos, Fernando C. [UNESP]; Landim-Alvarenga, Fernanda C. [UNESP] (My University, 2015)
Nanotechnology techniques have a prominent role in the current technical and scientific scene. The layer-by-layer (LbL) deposition allows obtaining nanostructures with sophisticated multilayer, using a simple, but versatile technique. This procedure, which is used to coat and functionalize surfaces with nanometer-thick films, has applications in bioengineering, medicine, chemistry, materials and chemical engineering among other areas. Chitosan is a biomaterial, coming from the chitin, a very abundant polymer in nature, which has been recently tested as scaffolds. In this experiment we test the hypothesis that the hyaluronic acid-chitosan polyelectrolyte multilayer biofilm would be a good substrate to the adherence of equine mesenchymal stem cells derived from bone marrow. The results showed that these biofilms accelerate the process of cell adhesion on smooth surfaces, allowing a constant cell growth and creating a great option to cover surgical materials.
Keywords: Bioengineering; Biofilms; Bone marrow; Chitosan; Hyaluronic acid; Layer-bylayer; Stem cells